Physical activity during pregnancy: benefits and global recommendations - Rovčanin, Marija (Medicinski podmladak, 2022)
Worldwide, physical activity (PA) is an essential factor in the prevention of noncommunicable diseases. Regular PA contributes to the improvement of most health parameters through improving many physiological, metabolic, and psychological parameters. PA is one of the crucial preconditions for the majority of human health requirements, particularly for the reproductive-aged population and pregnant women. PA during pregnancy has a beneficial impact not only on the well-being of the pregnant mother but also on the health of the baby. There are presently no official national guidelines regarding PA during pregnancy in Serbia, so we advocate and adhere to the worldwide norms. The widespread agreement is that every woman, excluding those with certain clinical or antenatal contraindications, should engage in PA throughout their pregnancy. Guidelines were developed with a special emphasis on the length, frequency, intensity, and type of PA that is recommended and those that should be avoided, as well as techniques for supervision with clearly defined indicators that indicate the need to discontinue a certain activity. Among pregnant women in Serbia, one of the most vulnerable demographic groups, PA has not been adequately implemented via initiatives aimed to improve this population’s overall health. Moreover, in Serbia, there have not been enough studies on the impacts and advantages of exercising during pregnancy, nor has there been sufficient speculation on the most appropriate method of advising pregnant women throughout their pregnancies. Future research may be required for the development and promotion of PA programs for pregnant women in an attempt to reduce pregnancy complications by providing specific guidelines regarding the importance and benefits of an active lifestyle during pregnancy and monitoring health-related attitudes and behaviors. Regarding the physiological changes associated with pregnancy, modest physical exercise during gestation looks healthy and should be promoted and strongly recommended.